Informal Street Vendors Survival Strategies during the Covid-19 Pandemic - Karen Joy Catacutan; Rona Jay Bernardo; Syra Angelyn Lumaday; Jessa Tabangcura; Justin Marc Benito; Gladys Tumbali (International Journal of Entrepreneurship, Business, and Creative Economy, 2023)
Due to the COVID-19 pandemic, our government has been forced to implement strict quarantine measures. As a result, social interaction, particularly among informal street vendors, has been restricted. The researchers undertook this study to learn more about the survival methods used by informal street vendors of Tuguegarao City, Cagayan. The current study used Interpretative Phenomenological Analysis as a qualitative research design. The informants in this study were 15 informal street vendors who were chosen through a random sampling technique. The data was gathered using an interview schedule. Two major findings were extracted from this study: (1) the effects of the COVID-19 pandemic are primarily negative to informal street vending businesses. In contrast, informal street vendors suffered from a decline in sales, inconvenience in selling, increased operating expenses, and disruption in operations. (2) Due to the resilience of the informants, they are able to cope-up by employing survival strategies such as adaptation of business strategies, policy adherence, and optimism. The results of the study will provide insights to the local government on how to possibly intervene in the affairs of the informal street vendors in order to contribute to the city's local development as they are part of the economy.